Efficacy and tolerability of zolmitriptan nasal spray for the treatment of acute migraine in adolescents: Results of a randomized, double‐blind, multi‐center, parallel‐group study (TEENZ). Issue 7 (22nd June 2016) - Winner, Paul; Farkas, Viktor; Štillová, Helena; Woodruff, Brian; Liss, Charlie; Lillieborg, Stefan; Raines, Shane; ,
Abstract : Objective: The primary objective of the TEENZ Study (NCT01211145) was to assess the efficacy of zolmitriptan nasal spray in the acute treatment of adolescent migraine patients (ages 12 to 17 years), as measured by the primary outcome variable of pain‐free status at 2 hours post‐treatment. Methods: This randomized, double‐blind, placebo‐controlled, four‐arm parallel group study compared zolmitriptan nasal spray with placebo in the treatment of a single episode of adolescent migraine. Patients completed a 30‐day run‐in period to treat a single migraine attack with single‐blind placebo nasal spray. Eligible patients, who had not responded to placebo, were randomized to one of three zolmitriptan nasal spray doses (5, 2.5, or 0.5 mg) or placebo in a ratio of 5:3:3:5 according to a computer‐generated randomization scheme. Patients completed diaries for 24 hours after treatment, recording headache pain scores, adverse events (AEs), and medications taken. Results: In an interim futility analysis, zolmitriptan nasal spray doses of 0.5 and 2.5 mg were declared futile relative to placebo and further randomization to these treatment arms was discontinued. Of 1653 patients enrolled into the study, 855 patients failed to meet study eligibility criteria and were considered screen failures. The most common reason for screen failure was response to placebo challenge (325 patients [38.0%]). Of the 798 patients who were randomized to treatment, 721 (90.4%) completed the study period. Of these, 657 (82.3%) treated a migraine within the study period and contributed data for analysis. Zolmitriptan nasal spray 5 mg was significantly more effective than placebo in achieving pain‐free status at 2 hours after treatment ( P  < .001), with 30% of patients achieving pain‐free status at 2 hours vs 17% of placebo‐treated patients (OR 2.18; 95% CI 1.40, 3.39). Zolmitriptan nasal spray 5 mg was also more effective than placebo in achieving pain‐free status at 3 and 4 hours post‐treatment (45 vs 24%, and 56 vs 39%; both P  < .001). Zolmitriptan nasal spray 5 mg was also more effective than placebo in achieving headache response at 2, 3, and 4 hours after treatment (51 vs 39%, 61 vs 48%, and 69 vs 57%, respectively; all P  ≤ .011). Zolmitriptan nasal spray was well‐tolerated at all doses. Dysgeusia was the most frequently reported AE, with greater frequencies reported in active treatment groups versus placebo. No serious AEs or AEs leading to discontinuation were reported. Most AEs were mild or moderate in severity, and consistent with the known profile of zolmitriptan in adult and adolescent populations. Conclusion: Zolmitriptan nasal spray was well‐tolerated in the acute treatment of adolescent (ages 12 to 17 years) migraine. Zolmitriptan 5 mg nasal spray demonstrated superior efficacy compared with placebo for the primary efficacy endpoint of pain‐free status 2 hours after treatment and the efficacy of the 5 mg dose was supported by the majority of secondary efficacy endpoints.